Cyberbullying detection using sentiment analysis in social media - Sintaha, Mifta; Satter, Shahed Bin; Zawad, Niamat; Swarnaker, Chaity; Hassan, Ahanaf (BRAC University, 2016)
Cataloged from PDF version of thesis report.